Relation between amino‐truncated amyloid beta peptide (AßN3–42 and AßN11–42) mitochondrial deposition and the activation of inflammation‐oxidative mechanisms in the lens epithelium in age‐related cataract from diabetic patients - Hernández‐Zimbrón, Luis Fernando; Ucharima‐Corona, Luis Eduardo; Tlapanco‐Beltrán, Cristina; Ferreyra‐Severo, Ezequiel; Ramirez‐Hernandez, Eleazar; Catorce‐Nava, Miryam (Alzheimer's & dementia, 2021)
Background AD is characterized by the formation of senile plaques and neurofibrillary tangles. Senile plaques are deposits of amyloid beta‐peptide 1‐42 (Aβ42) and another species of amyloid peptides known as amino‐truncated (N‐truncated) species; AßN3–42 and AßN11–42. These peptides cause neuronal and synapse loss. Age‐related cataract (ARC), the opacification of the crystalline lens, is one of the leading causes of blindness in the world. It has been reported the presence of amyloid peptides in teens capsule form ARC patients. However, the intracellular localization and rol of these peptides in the anterior capsule (lens epithelial cells) have not been described yet as well as the possible mechanisms involved. The aim of this study was to determine the correlation between the presence of N‐truncated species in the anterior lens capsule of diabetic (DP) and nondiabetic patients (NDP) with age‐related cataract (ARC) and pro‐inflammatory and oxidant markers. Method Informed consent was obtained from all patients. Samples were collected from 30 age‐related cataract from DP over 50 years of age with LOCS II score of nuclear color ≥4 along with 30 ARC from NDP’ subjects after phacoemulsification surgery. Lens capsules, were processed for IMH, IF, WB and dot blot . Monoclonal anti‐Aß‐1‐42, anti‐AßN3–42 and anti AßN11‐42, were used. anti‐VDAC, anti‐TSPO, anti‐TOM‐20, were used in double immunofluorescence assays to detect amyloid peptides in mitochondria. anti‐IL‐6, anti‐TNF‐a, anti‐IL‐17, anti‐ IL‐10, anti‐INF‐γ were used as inflammation markers and anti‐SOD, anti‐catalase and anti‐glutathione were used to detect oxidative changes in ARC. For WB and dot blot assay individual capsules were collected from each group were used. Result The results show the presence of Aβ42, AßN3–42 and AßN11–42 peptides in the mitochondria from cells of the anterior lens capsule from DP. There are statistically differences in the accumulation of AßN3–42 in mitochondria from ARC from DP. Inflammatory as well as oxidative markers show the activation of both pathological pathways and a positive correlation between them. Conclusion There is a correlation between amyloid peptides accumulation and the activation of pathological pathways on lens capsules in diabetic patients and these N‐truncated peptides detection in the eye could be useful as AD early diagnostic.